Drying characteristics of banana: theoretical modelling and experimental validation - Karim, M A; Hawlader, Mohammad Nurul Alam (Elsevier, 2005)
The post-harvest losses of agricultural products can be reduced drastically by using proper drying techniques. In the present study, a mathematical model for drying of food products undergoing shrinkage has been developed. The model, which includes the influence of both material and equipment, is capable of predicting dynamic behaviour of the dryer. Heat and mass transfer equations are solved simultaneously using a numerical technique. The material model is capable of predicting the instantaneous temperature and moisture distribution inside the material. The equipment model, on the other hand, describes the transfer process in the tunnel dryer and predicts the instantaneous temperature and humidity ratio of air at any location of the tunnel. For evaluation purposes, the model was applied to drying experiments in the range of air temperatures between 40 and 60 C and air velocity between 0.3 and 0.7 m/s. A tunnel type fruits dryer was used to conduct experiments. The prediction of the average moisture content and material temperature compared favourably with the experimental results. The predicted air temperature and humidity ratio of a batch type tunnel dryer also agreed fairly well with the experimental results. The model is capable of predicting dynamic behaviour of drying of fruits undergoing shrinkage and, as such, it can be used as a design tool. A parametric study was also conducted to examine the effect of different operating variables on drying potential and drying time.